Comparative study of different SES neighborhood clinics for health literacy and internet access. (September 2022) - Livingood, William C; Bautista, Maria A B; Smotherman, Carmen; Azueta, Daidre; Coleman, Jeremy; Grewal, Reetu; Stewart, Eric; Orlando, Lori A.; Scuderi, Christopher
Background: As healthcare services are increasingly dependent on patient utilization of technology to effectively deliver services, the digital divide has the potential to exacerbate health disparities if health literacy and internet access present formidable barriers to patient use of technology. Methods: We examined the differences in health literacy and internet access between lower and upper SES neighborhood primary-care clinics in Northeast Florida. The REALM-SF for health literacy was used to assess health literacy and census survey questions were used to assess internet and technology access, during the Fall, 2020. The clinics were affiliated with a safety-net hospital in a major city in Southeastern U.S. Results: Analysis of key demographic data confirmed that the responding patients from economically disadvantaged neighborhood clinics resided in economically disadvantaged zip codes (307 responding patients lived in lower SES neighborhoods) and did have lower education levels (3% of the patients from Upper SES clinics had 11 grade or lower education, compared to 21%–29% of patients from Lower SES clinics). Patient health literacy significantly differed between clinics located in economically disadvantaged neighborhoods and clinics located in more affluent neighborhoods, with Upper SES clinics being 2.4 times more likely to have 9th grade or higher reading level. Access to internet technology was also higher in the Upper SES clinics, with 59% of respondents from Upper SES clinics versus 32%–40% from Lower SES clinics owning a computer or an IPAD. Conclusion: Results of this study have important implications for patient-engaged use of digital technology for health. Healthcare and public health clinics should be aware of the difference in health literacy and internet access when implementing technology-based services, so that advances in medicine, including precision medicine and telehealth, can be disseminated and implemented with broad populations, including disadvantaged groups.